IDENTIFICATION OF CARRIERS OF YELLOW YR5, YR10, YR15 AND LEAF LR26, LR34 RESISTANCE GENES UNDER MOLECULAR SCREENING OF WHEAT ENTRIES - Kokhmetova , A.M.; Sapakhova , Z.B.; Madenova , A.K.; Yessenbekova , G.T. (Eurasian Journal of Applied Biotechnology, 2014)
Wheat rust diseases are a major cause of yield losses of this crop. Yellow (Puccinia striiformis f. sp. tritici) and leaf (Puccinia recondita Rob.et Desm f. tritici Eriks) rusts are of the most widespread and dangerous diseases of wheat and are the major factor that adversely affects wheat yield and quality and causes considerable economic damage. Use of genetic host resistance is the most effective, economical and environmentally safe method of controlling stripe rust that allow to eliminate the use of fungicides and minimize crop losses from this disease. Due to the threat of development epiphytoties rust disease it is necessary to identify new donors of resistance to yellow and leaf rust and creation on their basis of wheat breeding material. As a result phytopathological assesses susceptibility to rust on infectious background we have selected a number of samples resistant to Puccinia striiformis and Puccinia recondita f. sp. tritici. In the present study, attention was drawn to the part of the effective resistance genes to yellow and leaf rust – Yr5, Yr10 Yr15, as well as gene complex Lr26/Sr31/Yr9/Pm8 and Yr18/Lr34, which were identified in the process of molecular screening of wheat germplasm. Using molecular markers gene Yr5 identified in 1 sample, Yr10 – in 5, Yr15 – in 2, complex of resistance genes Lr26/Sr31/Yr9/Pm8 – in 3 and gene complex Yr18/Lr34 – in 6 samples. The most valuable donors of rust resistance are cultivars Mereke 70 and Akdala with 2 identified rust resistance genes. In cv. Mereke 70 highly efficient genes Yr10 and Yr18/Lr34 and in cv. Dastan Yr10 and Yr15 were identified. The results are used in Kazakhstan to create yellow and leaf rust resistant wheat varieties using MAS breeding. Our results provide an opportunity to move the breeding process in Kazakhstan to a new scientific level through the use of technology Marker Assisted Selection.